ANALISIS ADOPTION RATE PENGGUNAAN MICROSOFT COPILOT DALAM KEGIATAN AKADEMIK MAHASISWA SURABAYA MENGGUNAKAN METODE EXTENDED TAM - Achmad Naufal Ferdiansyah; Taqiyuddin Ahmad Al Aufa; Ahmad Faiq Shalahuddin Wafa (Jurnal Teknologi Informasi dan Komputer, 2026)
The advancement of artificial intelligence (AI) technology has introduced Microsoft Copilot as a supportive tool for students' academic activities. This study aims to analyze the factors influencing the adoption rate of Microsoft Copilot Bing among university students in Surabaya using the Extended Technology Acceptance Model (Extended TAM). A quantitative approach was employed through a Likert-scale questionnaire distributed to 100 purposively selected respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that Attitude Toward Use Copilot serves as a central mediator that significantly affects Intention to Use Copilot. Key predictors influencing this attitude include Perceived AI Enjoyment, Usefulness, and Intelligence. However, Perceived AI Trust and Personal Competence did not show a direct significant effect on users’ attitudes. To address discriminant validity issues, a model refinement process was conducted by simplifying overlapping indicators. The results highlight the importance of enjoyable user experiences, perceived usefulness, and AI intelligence in shaping students’ intention to adopt the technology. This research provides practical implications for technology developers and educational institutions in designing strategies to integrate AI-based tools effectively in academic environments.